Sharing our future : Canadian international development (CIDA Hull, QuebecCA, 1987)
Outlines conditions of crisis and world poverty that highlight need for enlightened Canadian aid policy. Indicates how the Canadian Government will enlarge and reform its ODA program and sharpen its focus and priorities. Discusses eligibility for Canadian aid and ways of improving aid delivery programs. Examines the formation of bilateral development partnerships between the Canadian Government and Canadian institutions and their counterparts in the third world. Outlines strategy to improve communication between development planners and the Canadian public.
Text in English and French